Mathématiques
luckyyy
3

URGENT!!!!!!! SVPP !!!!!!

+0
(1) Réponses
laurianne3838

1) a/ l aire  ABCD= (2x+1)²                             =4x²+4x+1 b/      l aire  ABEF= (2x+1)*(x+3)                             = 2x²+7x+3 c/ donc lair FEDC = lair ABCD- lair ABEF                              = (4x²+4x+1) - (2x²+7x+3)                              = 2x²-3x-2            (1) 2)a/ [FD]= [DA] - [FA]             = (2x+1) - (x+3)             = x-2 3/ l aire FECD = (x-2)*(2x+1)                         =2x²-3x-2     (2)   les deux expressions (1) et (2) sont égaux                               

Ajouter une réponse